1983
DOI: 10.1007/bf02226897
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of hot-humid and hot-dry environments on mental functions

Abstract: Twenty five subjects acclimatised to heat artificially were exposed to "basic effective temperatures" (BET) of 25.0 degrees, 29.6 degrees, 32.2 degrees, 33.3 degrees and 35.0 degrees C BET under conditions of both humid and dry heat. The object of the investigation was to ascertain the nature of effects of varying degrees of heat stress on mental alertness, associative learning, reasoning ability and dual-performance efficiency. A further aim was to determine the temperature levels at which impairment of psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Gopinhathan et al [5] found that, after recovery from exercise in the heat, soldiers demonstrated significant and progressive reduction in the performance of arithmetic ability, short‐term memory, and visuomotor tracking at a body fluid deficit of 2% or more compared to the euhydrated state. Sharma et al [6,7] detected the effects of dehydration at various levels (1, 2, and 3% of body weight deficit) on mental functions of different complexities in adults. They found that, at a 1 % dehydration level, there was only a marginal decline in the mean score of the coordination function, but at the 2 and 3% dehydration level, the performance score was significantly lower compared to the eu‐ and 1 % dehydration level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gopinhathan et al [5] found that, after recovery from exercise in the heat, soldiers demonstrated significant and progressive reduction in the performance of arithmetic ability, short‐term memory, and visuomotor tracking at a body fluid deficit of 2% or more compared to the euhydrated state. Sharma et al [6,7] detected the effects of dehydration at various levels (1, 2, and 3% of body weight deficit) on mental functions of different complexities in adults. They found that, at a 1 % dehydration level, there was only a marginal decline in the mean score of the coordination function, but at the 2 and 3% dehydration level, the performance score was significantly lower compared to the eu‐ and 1 % dehydration level.…”
Section: Discussionmentioning
confidence: 99%
“…This results in a state of dehydration as evidenced by a high urine osmolality (Uosm). Voluntary dehydration has adverse physiological effects [3,4] and may have adverse cognitive effects [5–7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High humidity often occurs when temperature is high, and the effects of the two exposures can be difficult to disentangle (Sharma et al 1983). In Germany, Schneider et al (2008b) analyzed the influence of weather parameters [including water vapor pressure (WVP)] on blood pressure, arrhythmia, and ischemia in cardiovascular patients.…”
Section: Introductionmentioning
confidence: 99%
“…2025 High humidity has been associated with declines in physical and mental capacity, but high humidity often occurs when temperature is high. 26 …”
mentioning
confidence: 99%